2009
DOI: 10.1002/j.1556-6678.2009.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a Contextual Perspective in the Application of the ACA Code of Ethics: The Ethics into Action Map

Abstract: Because community counselors work within an increasingly broad array of practice settings, it is imperative for them to understand how to apply the ACA Code of Ethics (American Counseling Association, 2005) to specific practice settings. The author examines ethics applied to unique practice settings and proposes the Ethics into Action Map as a method to promote an increased understanding of the application of ethical standards to specific contexts. Case examples are provided to illustrate the use of the Ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…The authors are in agreement with the participants of this research that ethics training distilled into a single ethics course is not adequate for preparing students. In addition to ethics courses, faculty should stress ethical decision-making (Calley, 2009) and case studies that emphasize ethical decisionmaking. (McCarron & Stewart, 2011;McGee, 2005) with students as frequently as possible across the academic program.…”
Section: Discussionmentioning
confidence: 99%
“…The authors are in agreement with the participants of this research that ethics training distilled into a single ethics course is not adequate for preparing students. In addition to ethics courses, faculty should stress ethical decision-making (Calley, 2009) and case studies that emphasize ethical decisionmaking. (McCarron & Stewart, 2011;McGee, 2005) with students as frequently as possible across the academic program.…”
Section: Discussionmentioning
confidence: 99%
“…In situated learning, students link course material with activities that (Granello, 2000). Approaching instruction and learning from a contextual framework has a number of benefits (Calley, 2009;Granello, 2000;Nelson & Neufeldt, 1998;Sears & Hersh, 1998;Toman & Rak, 2000). Calley (2009) noted that using case examples helps students move from inactive to active learning; for example, rather than simply reviewing ethical standards, students must apply standards to practice in case examples.…”
Section: Ethics Instructionmentioning
confidence: 96%
“…Approaching instruction and learning from a contextual framework has a number of benefits (Calley, 2009;Granello, 2000;Nelson & Neufeldt, 1998;Sears & Hersh, 1998;Toman & Rak, 2000). Calley (2009) noted that using case examples helps students move from inactive to active learning; for example, rather than simply reviewing ethical standards, students must apply standards to practice in case examples. Toman and Rak (2000) suggested that as programs adapt to changing times, contextual teaching styles may engage both educators and students in the learning process.…”
Section: Ethics Instructionmentioning
confidence: 97%
See 1 more Smart Citation
“…Researchers have examined ethics within the frameworks of diagnosis (Dougherty, 2005;Kress, Hoffman, & Eriksen, 2010), testing and assessment (Naugle, 2009), spirituality (Steen, Engles, & Thweatt, 2006), therapeutic prayer (Weld & Eriksen, 2007), and computer-based supervision (Vaccaro & Lambie, 2007). The literature also contains examples of ethics decision-making models and recommendations to assist professionals in navigating the complexities of ethics dilemmas (Barnett, Behnke, Rosenthal, & Koocher, 2007;Burkholder, Toth, Feisthamel, & Britton, 2010;Calley, 2009;Freeman & Francis, 2006;Foster & Black, 2007;Glosoff, Herlihy, & Spence, 2000). Undoubtedly, a diversity of perspectives and attitudes exist within the helping professions concerning ethics, ethics codes, and how ethics apply within a variety of contexts.…”
Section: Defining and Exploring Ethicsmentioning
confidence: 99%